The right to remain - Grippando, James, 1958- (Grippando, James, 1958- Jack Swyteck novel, 2026)
"Miami criminal defense lawyer Jack Swyteck must contend with a unique problem. His client, Elliott Stafford, indicted for murder, has gone silent. Not just silent in asserting his Fifth Amendment right against self-incrimination--Elliott refuses to speak. He won't talk to the judge, his girlfriend, or even the attorney fighting for his life. There seems to be no medical or psychological reason for his silence. He has, as Jack puts it, 'chosen to become his own worst enemy.' To some, it's an act of protest against a broken criminal justice system. Jack doesn't buy it. Undeterred by the hoopla and calls to walk away, he keeps his client and tries his best to save Elliott from himself. As he digs for facts, Jack discovers a much more disturbing reason for Elliott's silence. Virtually everything Elliott told Jack before the indictment is proving false, including Elliot's criminal history, family turmoil, and secret past. As Jack plunges deeper, he comes to believe that Elliott isn't trying to hide his own guilt. He may be protecting someone else--and the stakes could not be higher"--